Democratisation and autocratisation: evidence from Latin America - Araujo, André Leite (Universidade Estadual Paulista (Unesp), 2026)
A pesquisa tem como objetivo identificar as causas dos processos de autocratização no século XXI, na América Latina. Neste trabalho, a pergunta de pesquisa é “O que causa padrões de declínio da democracia na América Latina nos últimos anos?” e as hipóteses são que a queda no padrão de vida da sociedade e a duração dos governos incumbentes aumentam o nível de autocracia. Para responder a essa pesquisa e testar as hipóteses, a metodologia foi estruturada em duas fases sequenciais – quantitativa e qualitativa. Na primeira etapa, a partir da formação de banco de dados, foi conduzida análise estatística de 13 países entre 2001 e 2022. Na etapa qualitativa, Brasil e El Salvador compuseram estudos de caso comparados. Confirmando as expectativas da pesquisa, a continuidade forçada no governo impulsiona a autocratização. Já o padrão de vida da sociedade pode ser instrumentalizado nos discursos de projetos autocratizantes. Adicionalmente, a variável de segurança pública foi um achado relevante para compreender tais dinâmicas políticas. Os resultados contribuem para a compreensão teórica desse fenômeno contemporâneo, através da análise empírica sobre a América Latina e de mecanismos que levam ao declínio da democracia.

The research aims to identify the causes of processes of autocratisation in the twenty-first century in Latin America. In this study, the research question is “What causes declining patterns of democracy in Latin America in the past years?”, and the hypotheses are that a decline in the living conditions and the duration of incumbent governments increase the level of autocracy. To address this question and test the hypotheses, the methodology was structured in two sequential phases — quantitative and qualitative. In the first phase, following the construction of a database, a statistical analysis of 13 countries between 2001 and 2022 was conducted. In the qualitative phase, Brazil and El Salvador were analysed as compared case studies. Confirming the research expectations, the forced continuation in power fosters autocratisation. The living conditions, in turn, can be instrumentalised in the discourse of autocratising projects. Additionally, the public security variable emerged as a relevant finding for understanding these political dynamics. The results contribute to the theoretical understanding of this contemporary phenomenon through empirical analysis of Latin America and of the mechanisms that lead to democratic decline.
Democratização e autocratização: evidências da América Latina
Keywords: América Latina; Autocratização; Brasil; Comportamento político; Democracia; Democratização; El Salvador; Eleições; Política comparada; Comparative politics; Elections; El Salvador; Democratisation; Democracy; Political behaviour; Brazil; Autocratisation; Latin America